2017
DOI: 10.15517/rbt.v65i3.29444
|View full text |Cite
|
Sign up to set email alerts
|

Variación arquitectónica y morfológica de Hintonia latiflora (Rubiaceae) en relación a la cosecha de corteza y factores ambientales

Abstract: Architectural and morphological variation of Hintonia latiflora (Rubiaceae) in relation to bark harvest and environmental factors. Hintonia latiflora is a rare ecologically and economically important species from the Tropical Deciduous Forest of the Balsas Basin, Mexico, whose bark is traded as medicinal. Debarking practices have modified the shape of plants, their architecture and morphometry; but it is unknown if some topographic and edaphic factors may also influence in these attributes. Here we propose tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
9
Order By: Relevance
“…Other factors that were not analyzed in this study but have been observed to have an impact on morphometric variation of vegetative and reproductive structures, were ground slope, soil depth, stony soil, temperature, wind speed, rain, and relative humidity [29,30]. In contrast, in other studies conducted in members of the genus Opuntia, it was determined that phenotypic differences in cladodes between populations were more related to population density than environmental factors [31].…”
Section: Morphological Variation In Wild Populationsmentioning
confidence: 67%
“…Other factors that were not analyzed in this study but have been observed to have an impact on morphometric variation of vegetative and reproductive structures, were ground slope, soil depth, stony soil, temperature, wind speed, rain, and relative humidity [29,30]. In contrast, in other studies conducted in members of the genus Opuntia, it was determined that phenotypic differences in cladodes between populations were more related to population density than environmental factors [31].…”
Section: Morphological Variation In Wild Populationsmentioning
confidence: 67%
“…Hintonia latiflora es una especie leñosa, iterópara y hermafrodita, protándrica y hercógama, polinizada por lepidópteros nocturnos y quirópteros, con dispersión anemócora y barócora (Beltrán-Rodríguez et al, 2015). Los individuos son reproductivos a partir de 8 cm de diámetro basal y, en estos, sus dimensiones alométricas van de 15 cm a 40 cm en diámetro basal, 6 m a 8 m de altura y ancho de copa de 3.5 m a 6.5 m, con una producción promedio de corteza en peso seco que oscila entre 500 g y 4 kg por individuo (Beltrán-Rodríguez et al, 2017b). Esta especie es endémica del bosque tropical caducifolio de México y Centroamérica (Lorence y Taylor, 2011), y presenta poblaciones aisladas con baja densidad de individuos reproductivos (5 ind.…”
Section: Especie De Estudiounclassified
“…El área está conformada por parches de vegetación compuestos por campos agrícolas y bosques secundarios en las planicies próximas al Río Balsas, así como bosques primarios relativamente bien conservados en las zonas montañosas más alejadas. La vegetación dominante es bosque tropical caducifolio con predominio de las familias Fabaceae, Burseraceae y Poaceae, pero también hay Matorral Xerófilo tipificado por cactáceas columnares (Beltrán-Rodríguez et al, 2017b).…”
Section: áRea De Estudiounclassified
See 1 more Smart Citation
“…The knowledge of the tree architecture and dasometric measurements represents a contribution to defining criteria for harvesting and management (Beltrán-Galindo, Romero-Manzanares, Luna-Cavazos, & García-Moya, 2017) and the design of agroforestry or silvicultural systems. The architecture of the tree canopy has significant impacts on the microclimate of the crop and is influenced by competition for light, water absorption and transpiration, dispersion of pollen; acquisition and location of carbon (Boudreau, 2013).…”
mentioning
confidence: 99%